ARCHAEAL LIPIDS AND ANAEROBIC OXIDATION OF METHANE IN EUXINIC WATER COLUMNS: A COMPARATIVE STUDY OF THE BLACK SEA AND CARIACO BASIN - Wakeham S.G.; Hopmans E.C.; Schouten S.; Sinninghe Damsté J.S. (My University, 2004)
The Black Sea and the Cariaco Basin are both large, euxinic marine basins in which methane concentrations are high and where anaerobic oxidation of methane (AOM) is an important part of the carbon cycle. AOM can be recognized by lipid biomarkers that are specific to methanotrophic archaea involved and by strongly 13C-depleted isotope compositions consistent with uptake of 13C-depleted methane-derived carbon. The working hypothesis for our investigation was that AOM in both the Black Sea and Cariaco Basin would generate measurable diagnostic biomarkers and isotope depletions. To test this hypothesis, we analyzed particulate matter and surface sediments for intact glycerol dialkyl glycerol tetreaethers (GDGTs), components of archaeal membrane lipids, and measured stable carbon isotope compositions of their constituent biphytanes. Several GDGTs and strongly 13C-depleted biphytanes indicative of AOM were present in the deep anoxic region of the Black Sea (>700 m). Unexpectedly, this biomarker signal was not detected in the upper anoxic zone of the Black Sea or in the entire water column of the Cariaco Basin, even though previous studies had shown high rates of AOM to occur in both basins. It is possible that the AOM-derived biomarker signal is masked by archaeal lipids derived from non-methanotrophic archaea which utilize 13C-enriched carbon substrates. Alternately we speculate that the methanotrophic community may be highly diverse in euxinic basins, possibly producing another suite of biomarkers that we did not measure. This conclusion will require further testing by coordinated organic geochemical–microbial ecology studies.